Impact of product assortment, perceived service quality, website quality, and customer reviews on customer happiness and word of mouth - Fayez Bassam Shriedeh; Jalal Rajeh Hanaysha; Osman Gulseven (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
The main aim of this paper focuses on examining the effect of website quality, product assortment, customer reviews, and perceived service quality on customer happiness and word of mouth. The data for this research was gathered from online shoppers of retail stores in United Arab Emirates. Data was analyzed using partial least square based structural equation modeling through SmartPLS software in order to verify research hypotheses and draw conclusions. The findings also showed that website quality, customer reviews and perceived service quality have positive effects on customer happiness and word of mouth. Finally, the results revealed that product assortment positively affects word of mouth, while its effect on customer happiness is insignificant. This research builds upon the existing literature by demonstrating the effect of selected factors on customer happiness and word of mouth, considering that only limited studies were conducted in the past about these variables in the Middle East region.
Keywords: 330; Product assortment; customer reviews; perceived service quality; online retail customers; website quality; customer happiness; word of mouth; United Arab Emirates